A communitarian microgrid storage planning system inside the scope of a smart city. (1st September 2017) - Coelho, Vitor N.; Coelho, Igor M.; Coelho, Bruno N.; de Oliveira, Glauber C.; Barbosa, Alexandre C.; Pereira, Leo; de Freitas, Alan; Santos, Haroldo G.; Ochi, Luis S.; Guimarães, Frederico G.
Highlights: Energy scheduling in mini/microgrids systems considering plug-in electric vehicles and drones. Sets of non-dominated solutions opening possibilities for smart cities managers. Smart cities citizens awareness for investing in alternatives energy based vehicles. Energy storage systems contributing for renewable energy integration with mini/microgrids. Abstract: In this paper (a substantial extension of the short version presented at REM2016 on April 19–21, Maldives[1] ), multi-objective power dispatching is discussed in the scope of microgrids located in smart cities. The proposed system considers the use of Plug-in Electric Vehicle (PEV) and Unmanned Aerial Vehicle (UAV) as storage units. The problem involves distinct types of vehicles and a community, composed of small houses, residential areas and different Renewable Energy Resources. In order to highlight possibilities for power dispatching, the optimization of three distinct goals is considered in the analysis: mini/microgrid total costs; usage of vehicles batteries; and maximum grid peak load. Sets of non-dominated solutions are obtained using a mathematical programming based heuristic (Matheuristic). By analyzing cases of study composed with up to 70 vehicles, we emphasize that PEVs and UAVs can effectively contribute for renewable energy integration into mini/microgrid systems. Smart cities policy makers and citizens are suggested to consider the proposed tool for supporting decision making for cities under development, guiding their choices for future investments on renewable energy resources.